Peran Kerapatan Adat Nagari dalam Perencanaan dan Pengawasan Pemerintahan Nagari pada Era Otonomi Daerah di Sumatera Barat - Fhariz El Habyb; Aldri Frinaldi; Lince Magriasti; Hendranaldi Hendranaldi (Policy, Law and Political Research Center, 2025)
This study analyzes the participation of indigenous communities in the implementation of regional autonomy in West Sumatra, particularly through the institutional role of the Nagari Customary Council (KAN). Regional autonomy in Indonesia, since the enactment of Law No. 22 of 1999 to Law No. 23 of 2014, has opened up space for nagari as a customary law community to contribute to regional development. This study uses a qualitative approach through literature review to examine the dimensions of indigenous peoples' participation in the planning, implementation, and supervision of nagari administration. The results of the study show that KAN plays a significant role in drafting nagari regulations, supervising the government, and channeling community aspirations. However, this participation is not yet optimal due to limited access to information, minimal involvement of customary institutions in the public policy process, and the dominance of local governments in the implementation of autonomy. Considering the limitations of literature studies, this research emphasizes the importance of strengthening the capacity of indigenous institutions, increasing the transparency of nagari governance, and multiparty collaboration as strategies to strengthen indigenous peoples' participation in the implementation of democratic and sustainable regional autonomy.